Bridging External Store Stimuli And Internal Psychological Drives To Increase Impulse Buying In Modern Stores - Kumala Dwi, Shinta; ali; Widiastuti, Anna (Cita konsultindo, 2026)
This research aims to analyze the influence of product diversity on impulse buying behavior, with hedonic shopping motivation acting as a mediating variable within a modern retail environment. Amidst a significant shift in consumer behavior toward seeking experience and pleasure , this study addresses a research gap in the Southeast Asian market by examining how an extensive assortment of brands, sizes, and product qualities often exceeding 18,000 items captures consumer attention and triggers unplanned purchases. The methodology involves an empirical analysis of consumer responses to external store stimuli and internal psychological drives. Findings reveal that product diversity has a positive and significant effect on both impulse buying and hedonic shopping motivation. Furthermore, hedonic shopping motivation serves as a vital mediator, as the results indicate that a broad product range is most effective in driving impulse purchases when it successfully generates a pleasant emotional drive in the consumer. These results offer practical implications for retail managers, suggesting that to stabilize fluctuating transaction data and counter decreasing impulse buying frequency, they must focus on creating an emotionally stimulating shopping experience that enhances sensory satisfaction.